CODES USED BY TWO PAIRS OF IDENTICAL TWINS - Wida F. Gunawan; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This study is about the codes used by two pairs of identical twins to their co-twin in their daily conversation. It is supported by Wardaugh’s (2006) and Stromswold’s theories (2004) of codes and language development. The data was gathered from the utterances produced in the given role plays. The findings reveal that seven types of codes were used by these pairs of twins. The similarities are all of them did not use secret language and both pairs mostly used Indonesian codes. The differences are the frequency of each code used and in general, Pair 2 is more formal than Pair 1. In conclusion, having Javanese parents does not always mean using Javanese codes when communicating with others and although they are twins, they do not always use similar codes. These differences might happen because of the differences in religion and travel experiences